The Effect of External Debt, Unemployment Rate, and Inflation on Economic Growth in Ghana - Evans, Yeboah (Journal of Empirical Studies, 2022)
Inflation and unemployment rates are part of the macroeconomic factors affecting growth within Ghana's economy over the years. The continued rise in the country's gross domestic product and a high dependency on external debt for development projects have sparked a lot of controversies. This study investigates whether external debt, inflation, and unemployment rate stimulate economic development, intending to determine the causal relationship between the variables to serve as an important factor for policymakers. The econometrics methods include the stationarity test, Johansen cointegration test, and regression (ordinary least squares). The data used was from the World Bank from 1991-2021. The stationarity test showed that external debt, GDP, and unemployment were non-stationarity and integrated at the first-order difference, whereas inflation was stationary at the level. The Johansen cointegration test found a long-run relationship between selected variables, but only external debt positively impacted economic growth in the long term. In contrast, inflation and unemployment had a negative impact. The regression results found external debt to be positively correlated to growth in Ghana, but inflation and unemployment harm it with GDP as the explained variable. The findings also indicate that external debt increased inflation, whereas GDP reduced inflation, but unemployment did not influence inflation. The outcome further proves that external debt positively impacted the unemployment rate, and GDP negatively influenced it.